2018
DOI: 10.5194/cp-14-1851-2018
|View full text |Cite
|
Sign up to set email alerts
|

Sedproxy: a forward model for sediment-archived climate proxies

Abstract: Climate reconstructions based on proxy records recovered from marine sediments, such as alkenone records or geochemical parameters measured on foraminifera, play an important role in our understanding of the climate system. They provide information about the state of the ocean ranging back hundreds to millions of years and form the backbone of paleo-oceanography.However, there are many sources of uncertainty associated with the signal recovered from sediment-archived proxies. These include seasonal or depth-ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 85 publications
0
74
0
Order By: Relevance
“…Simple models parametrizing the foraminiferal flux as a function of environmental parameters (Mix, ; Schmidt & Mulitza, ; Roche et al, ; Dolman & Laepple, ) might allow first‐order estimates of these ecological effects. Further, more complex ecosystem modeling that also includes the interaction of secondary parameters such as nutrients has the potential to provide indications on how seasonality and habitat depth change in a different climatic setting (Kretschmer et al, ; Lombard et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Simple models parametrizing the foraminiferal flux as a function of environmental parameters (Mix, ; Schmidt & Mulitza, ; Roche et al, ; Dolman & Laepple, ) might allow first‐order estimates of these ecological effects. Further, more complex ecosystem modeling that also includes the interaction of secondary parameters such as nutrients has the potential to provide indications on how seasonality and habitat depth change in a different climatic setting (Kretschmer et al, ; Lombard et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…While the first assumption that chlorophyll and primary productivity are related is probably accurate on 1st order (Henson et al, 2010), the relationship between primary productivity and export productivity is less trivial. Previous studies have identified a general relationship between export productivity, marine productivity, and sea surface temperature (Dunne et al, 2005;Laws et al, 2011). Sediment trap studies done in the Santa Barbara and Guaymas basins generally show a similar pattern (Thunell et al, 1994;Thunell, 1998), with export production correlated positively with primary productivity (organic carbon and opal in the Santa Barbara Basin; opal in the Guaymas Basin).…”
Section: Limitationsmentioning
confidence: 99%
“…Improved model resolution can also help proxy-model comparison in those regions where, for example, local currents are poorly resolved (Saba et al, 2016). Other major advances could come with a more extensive use of proxy system forward models (Dee et al, 2016;Dolman & Laepple, 2018;Evans et al, 2013;Kretschmer et al, 2018), in particular in the context of the last millennium. For example, one of the avenues currently explored is the explicit modeling of other parts of the climate system, such as water isotopes (Sjolte et al, 2011;Stevenson et al, 2013;Werner, Langebroek, et al, 2011).…”
Section: Paleoceanography and Paleoclimatologymentioning
confidence: 99%